PENINGKATAN PENGETAHUAN DALAM UPAYA PEMBERDAYAAN IBU DALAM PEMANTAUAN TUMBUH KEMBANG MELALUI KELAS BALITA - Tarsikah; Lisa Purbawaning Wulandari (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
Mothers have an important role in monitoring the growth and development of toddlers which is facilitated through posyandu and toddler mother classes, but empirical facts show that the presence of parents at posyandu decreases when their toddlers have finished receiving immunizations. The purpose of the activity is to increase parents' knowledge in monitoring the growth and development of toddlers through mother toddler class. This activity was carried out with a participatory approach, which was divided into 3 stages, namely preparation, implementation and evaluation. The target of the activity is 5 mothers of toddlers who have children aged 1-2 years. At the preparatory stage, a preliminary study was carried out, it was found that there was a problem of decreasing the frequency of mothers attending the posyandu. At the implementation stage: discussing material about the growth and development of toddlers aged 1-2 years and healthy snacks. The results of growth and development monitoring showed that 1 toddler needed a referral to the Puskesmas. Evaluation of activities shows the active participation of participants in class activities for mothers of toddlers as shown by 4 out of 5 mothers asking questions during discussions. It is hoped that this activity can be followed up with the behavior of mothers to attend the posyandu in order to monitor the growth and development of their toddlers